Analysis of The Fiscal Reconciliation Treatment of PT NA in The Determination of Corporate Income Tax - Ida Bagus Gede Okta Wismajaya; Putu Purnama Dewi (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The implementation of the self-assessment tax system in Indonesia is often hindered by regulatory complexity, which triggers compliance issues related to Corporate Income Tax. This phenomenon is highlighted in PT NA, a subsidized LPG distributor, which experienced significant divergence between commercial and fiscal financial statements due to subsidized and non-subsidized transactions. The main objective of this study is to analyze the causes of these differences and examine the implications of the fiscal reconciliation process on the calculation of payable Corporate Income Tax. A quantitative-qualitative case study was conducted at PT NA using the 2021 financial statements that had not been optimally reconciled. The analysis was carried out by comparing commercial Profit and Loss with tax regulations (Article 6 and 9 of the Taxation Law). The main results show the existence of Positive Fiscal Adjustments amounting to IDR 8,978,421,881 and Negative Fiscal Adjustments amounting to IDR 9,046,380,000. These adjustments changed the Taxable Income to IDR 870,136,000 and Underpaid Tax to IDR 133,314,700, indicating substantial adjustments from the initial report. It is concluded that fiscal reconciliation is highly crucial and significantly changes the amount of payable Corporate Income Tax. Inaccuracy in this process risks triggering disputes and fiscal sanctions. Practically, this study serves as an important reference for PT NA and similar entities to reconstruct accurate fiscal reports in order to ensure tax compliance.